Photoelectric properties of the photoconducting film composites based on ferrocenyl‐ and carbazolyl‐containing oligomer doped with polymethine dye: Fotoelektrische Eigenschaften von fotoleitenden Verbundfilmen auf Basis von ferrocenyl‐ und carbazolylhaltigem, mit Polymethinfarbstoff geimpftem Oligomer. Issue 4 (9th April 2016) - Davidenko, N. A.; Davidenko, I. I.; Ishchenko, A. A.; Kravchenko, V. V.; Mokrinskaya, E. V.; Studzinsky, S. L.; Tonkopieva, L. S.
Abstract : New photosensitive polymeric film composites based on oligomer containing ferrocenyl and carbazolyl fragments doped with symmetric polymethine dye are synthesized. Their photoelectric properties are investigated. Photovoltaic properties of these composites are detected. The mechanisms and peculiarities of the photovoltaic and photodielectric effects are discussed.